Hukum Keluarga Islam Di Indonesia Dalam Diskursus Ketidaksetaraan Gender - Hayati, Ilda; Edyar, Busman; Sanjaya, Rhandi (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims to explain the concept of the Islamic family which is linked to the discourse of gender equality. The type of research is normative juridical with a fiqh approach and statute approach which is analyzed by means of prescriptive analysis. The results of the research found that Islamic family law (both in Islamic fiqh and the Compilation of Islamic Law) has a concept of gender relations that is different from the paradigm built by gender equality activists. This can be seen from the relationship between husband and wife and their respective rights and obligations (including polygamy), the existence of a marriage guardian for female brides (but not vice versa), the requirement of witnesses who count one man to two women, the provision of iddah for a woman whose marriage has ended, to the unequal share of inheritance between men and women where men get a share of two to one compared to daughters.